2023
DOI: 10.3389/fpsyg.2022.1010442
|View full text |Cite
|
Sign up to set email alerts
|

The home language environment and early language ability in rural Southwestern China

Abstract: Using premier Language Environment Analysis technology to measure and analyze the home language environment, this observational study aims to describe the home language environment and child language ability, drawing on empirical data from 77 households with children aged 18–24 months from rural China. The results show large variation in measures of the home language environment and early language ability, similar to other rural Chinese samples. Results also demonstrate significant correlations between child a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…The same study additionally found that adult-child conversation significantly predicted child language skill, even after controlling for other measures of parental stimulation [38]. This was supported by another study which also found measures of the home language environment to be significantly correlated with child language skills after controlling for other indicators of parental stimulation [39].…”
Section: Introductionmentioning
confidence: 63%
“…The same study additionally found that adult-child conversation significantly predicted child language skill, even after controlling for other measures of parental stimulation [38]. This was supported by another study which also found measures of the home language environment to be significantly correlated with child language skills after controlling for other indicators of parental stimulation [39].…”
Section: Introductionmentioning
confidence: 63%
“…These quantities are widely measured using the Language Environment Analysis (LENA™) system, a small recording device and software used to conduct unintrusive observation of the HLE (Gilkerson & Richards, 2009). Using LENA, many studies from low-, middle-, and high-income settings have found that infants who grow up in households with richer HLE (characterized by more adult speech and more adult-child interactions) learn vocabulary faster, demonstrate increased processing speed, and develop stronger language skills (Gilkerson & Richards, 2009;Weber et al, 2017;Zhang et al, 2023). Thus, the HLE is a strong predictor of language development (Gilkerson et al, 2018;Ramírez-Esparza et al, 2014;.…”
mentioning
confidence: 99%
“…One widely used and validated assessment for child language development is the MacArthur-Bates Communicative Development Inventories (CDI;deMayo et al, 2021;Frank et al, 2021). Studies have repeatedly found measures of the HLE to be associated with higher CDI scores, including adult speech (Ma et al, 2023), adult-child conversation (Ma et al, 2023;Ramírez et al, 2020;Zhang et al, 2023), and child vocalizations (Zhang et al, 2023). Understanding the HLE, therefore, can help researchers pinpoint the factors that impact children's language development and their long-term outcomes by extension.…”
mentioning
confidence: 99%